Efektivitas Komunikasi Pemasaran Properti Melalui Media Email Blast - Agustin, Dinda Putri; Wijaya, Abung Supama (Petanda: Jurnal Ilmu Komunikasi dan Humaniora, 2025)
The rapid development of digital technology has significantly transformed marketing communication strategies, including in the property industry. One widely used strategy is email blast, which enables businesses to reach their target audience quickly, personally, and efficiently. This study aims to analyze the effectiveness of property marketing communication through email blast media and to identify its role in increasing client engagement and loyalty. The research uses a descriptive qualitative approach by collecting data through observations during the internship program and literature studies. The findings show that email blast not only expands promotional reach but also allows companies to personalize content and analyze campaign performance in real-time. This strategy has a positive impact on improving customer engagement and loyalty. Therefore, email blast can serve as an effective marketing communication tool for property companies to remain competitive in an increasingly dynamic market. In addition, this study also provides insights for property marketing practitioners to optimize their digital communication strategies. The results of this study are expected to serve as a reference for companies in utilizing email blasts more strategically to enhance the effectiveness of marketing campaigns and strengthen long-term relationships with customers.